The management of ex-Department of Education and Training and ex-Model C schools in Cape Town: A description of policy and practice. - Baguley_LM (Department of Social Development, 2024)
This quantitative study seeks to understand the management used in four "ex-DET" schools, and four "ex-Model COl schools, now both termed pubic schools of Cape Town, South Africa. Part of the study questions whether South Africa's former apartheid laws, which resulted in Bantu education, still impacts on school management today. Three staff members from each of the four former Department of Education ("ex-DET" or "Black") schools, as well as three staff members from each of the four former "ex-Model C" ("White") schools were asked to participate. That included each of the schools' principals, the schools' development officers, and another senior manager nominated by the respective school principal. Each was asked to complete a self-administered questionnaire which I had drawn up after extensive reading and research on the subject. This reading included looking at international management authors' work, school-specific management research, the history of education in South Africa, and current South African school management policies. The main current South African school management policies used in this study include: the South African Schools Bill (1996), the Second White Paper on School Organisation, Governance and Funding (1996), the Whole Schools Evaluation Policy (2000), the Collective Agreement on Integrated School Management Systems (2003), the Educators Employment Act (1994), and resolutions to the Educators Employment Act (1994). The questionnaires were predominantly comprised of closed questions, with a few open-ended ones being incorporated so as to be able to gain a little more insight in certain areas. After having met the respondents and dropping off the questionnaires, they were then collected on completion. The data was captured through the use of a process using excel spreadsheets before I was able to begin reflecting and deducing conclusions from it. I began by identifying norms for each category of school's management, and then comparing them against one another. The results showed that different styles of management and perceptions were present between the two (ex-DET and ex-Model C) groups, of eleven respondents each. The majority of all twenty-two respondents indicated that they feel apartheid still affects their schools current means of management. Conclusions were drawn in chapter five and then recommendations for the Department of Education, ex-Model C schools, ex-DET schools, and further researchers were made accordingly.